2012
DOI: 10.1007/s13592-012-0127-z
|View full text |Cite
|
Sign up to set email alerts
|

Vector integration and novel shortcutting in honeybee navigation

Abstract: -Honeybees that had been trained to visit two feeders simultaneously were released at five sites located further away from the training area. Harmonic radar tracking was used to record the complete homing flights. The bees performed multiple straight flight components (SFCs) between curved search flights. SFCs reflect vector directions between the two feeding sites and the respective vectors between the feeding sites and the hive. Direct flights back to the hive were also observed. The latter belong to a homin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
18
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Interestingly, the greatest treatment effect was measured during poor weather conditions in environments with a greater density of landmarks (Fig. 2b), suggesting that treated foragers had greater difficulties to recover and integrate the information on vector flights among learned landmarks and/or to derive novel shortcut vector flights 18,19 . This also matches the recent evidence from harmonic radar tracking surveys that honeybees experience difficulties in their homing flight pattern after non-lethal exposure to neonicotinoid pesticides 28 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, the greatest treatment effect was measured during poor weather conditions in environments with a greater density of landmarks (Fig. 2b), suggesting that treated foragers had greater difficulties to recover and integrate the information on vector flights among learned landmarks and/or to derive novel shortcut vector flights 18,19 . This also matches the recent evidence from harmonic radar tracking surveys that honeybees experience difficulties in their homing flight pattern after non-lethal exposure to neonicotinoid pesticides 28 .…”
Section: Discussionmentioning
confidence: 99%
“…Herein, Navigation Evironmental Correlate, thereafter abbreviated as NECs, refer to those extrinsic drivers of bee navigation and flight performances, comprising weather conditions (temperature, cloudiness or visibility of sun) and salient landmarks acting as visual cues for orientation [13][14][15][16][17][18][19][20][21][22] . Homing honeybees rely on a network of learned interconnected vectors for orientation 18 , conceptualized as memorized distances and directions among known locations.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Orienting to laboratory simulations of local geomagnetic fields, Caribbean spiny lobsters can accurately orient toward their home den (74). Studies of cognitive mapping in honey bees by Menzel et al have shown that displaced honeybees can initiate homing flights from any location within the explored area along novel shortcuts and can choose among at least three goals (75,76). Honeybees can also shortcut between vectors learned from exploration and those learned from the waggle dance (77).…”
Section: Arthropodsmentioning
confidence: 99%